Limites e intersecções do estético com o político no filme Janela indiscreta, de Alfred Hitchcock, e no conto "Sessão das quatro", de Roberto Drummond - Wanderlan da Silva Alves (Estudos de Literatura Brasileira Contemporânea)
We analyze the short-story “Sessão das quatro”, by Brazilian writer Roberto Drummond, and the movie Rear Window, by Alfred Hitchcock. We discuss the language of narratives, focusing some points of borders and intersections between aesthetical and political elements in the construction and representation of forms of power. The characters of these narratives are inserted in the lands where the idea of public or private space is diffuse, the freedom is besieged, and the violence forms some structural elements of the reality. Then, the creation of alternative places for the enunciation gives to characters some possibilities for a critical action in that space where the concepts of law and ethic constitute the exception.